(untitled) (BIRDEM Medical Journal, 2019)
Background: Chikungunya is a rapidly spreading viral infection of global concern. Initial presentation of chikungunya infection is often indistinguishable from other viral infections. In Bangladesh, chikungunya is an emerging infection. In this report, we describe socio-demographic, clinical and laboratory characteristics of chikungunya in a selected group of Bangladeshi patients. Methods: A multi-center descriptive study was done including adult patients with chikungunya virus infection from July 1, 2017 to October 31, 2017. Diagnosis of chikungunya virus infection was confirmed by reverse transcriptase polymerase chain reaction (RT-PCR) or immunoglobulin M (IgM) against chikungunya. Results: Total patients were 107 including 61 (57%) males. Mean age of the study participants was 35.6 (range 19-84) years. Ninety three (86.9%) patients presented with fever and 14 (13.1%) patients (with history of recent fever) presented due to joint pain. Most (93, 86.9%) patients were managed as out-patient basis; while 14 (13.1%) patients required hospitalization. Common features were fever/history of fever, joint pain, rash and lymphadenopathy. Out of 93 patients who presented with fever, 79 (85%) had concomitant arthralgia/ arthritis, 70 (75.3%) had persistent joint symptoms beyond febrile illness requiring paracetamol, 63 (67.2%) patients had joint pain beyond 3 weeks (sub-acute phase) requiring paracetamol, non-steroidal antiinflammatory drugs or corticosteroids and 11 patients had passed 3 months since symptom onset (chronic phase) and only one (9%) had joint symptoms requiring hydroxychloroquine. There was no death. Conclusion: Clinical manifestation of chikungunya virus infection was comparable with other viral infections but arthritis/arthralgia was an important differentiating point. As chikungunya is an emerging infection in Bangladesh, physicians should have a high index of suspicion and care should be taken to exclude other viral infections specially dengue. Birdem Med J 2019; 9(2): 106-110